2016
DOI: 10.3748/wjg.v22.i28.6547
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of functional gastrointestinal disorders in infants and toddlers: A systematic review

Abstract: The scarcity and heterogeneity of FGID data call for the necessity of well-designed epidemiological research in different levels of pediatric practice and refinement of diagnostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
8
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 49 publications
4
52
8
7
Order By: Relevance
“…Rates of infantile colic have been previously reported to be between 1 and 28% worldwide . We found a 23% prevalence rate, which was higher than the 11% found in our previous study from three Colombian cities.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Rates of infantile colic have been previously reported to be between 1 and 28% worldwide . We found a 23% prevalence rate, which was higher than the 11% found in our previous study from three Colombian cities.…”
Section: Discussioncontrasting
confidence: 82%
“…We found that 40% of the infants fulfilled the Rome III criteria for at least one FGID diagnosis with 8% qualifying for more than one FGID diagnosis. Wide‐ranging rates of FGID (1–25%) have been reported by studies on infant regurgitation . For example, a population‐based study from Italy that relied on paediatricians to report child symptoms found a prevalence of 12% for infant regurgitation, which was slightly higher than our data , and van Tilburg et al found an even higher prevalence of regurgitation (26%) in American infants .…”
Section: Discussioncontrasting
confidence: 74%
“…Reported prevalence rates of FGIDs in neonates and toddlers vary between 27.1% and 38.0%, with the most prevalent disorders being infant regurgitation and functional constipation (1-25.9% and 1-31%, respectively) [7]. Infants and toddlers with an FGID display a reduced quality of life and visit medical professionals more often compared to healthy controls [8].…”
Section: Impactmentioning
confidence: 99%
“…1,2 The prevalence of constipation varies depending on the diagnostic criteria used, and it is considered to be a public health problem. 3 The Rome criteria are currently adopted to standardize the diagnosis of constipation in the pediatric population. 4,5 An important role of retention behavior has been evidenced in the pathophysiology of functional constipation, due to unpleasant experiences with bowel movements.…”
Section: Introductionmentioning
confidence: 99%